Rhetorical Structure and Reader Manipulation in Agatha Christie's Murder on the Orient Express - Alexander, Marc (Miscelánea: A Journal of English and American Studies, 2009)
This paper describes Agatha Christie’s use of rhetoric to convince readers of the ‘truth’ of her detective’s solution in The Murder on the Orient Express, and uses an adaptation of Rhetorical Structure Theory (RST) designed for analyses of long extracts of a narrative text. The paper aims to demonstrate firstly the rhetorical practice of Christie, and secondly to demonstrate a tabular, non-diagrammatic exposition of RST, with some suggestions for future alterations to this method.